Gut-muscle axis crosstalk in age-related sarcopenia: mechanisms and therapeutic targets - Gao, Ling-Li; Chen, Yan; Dai, Ting; Zheng, Jie; Su, Shuo-Shuo; Chen, Yi-Xun; Chen, Li-Dian; Gao, Jing; Feng, Xiao-Dong (Frontiers in Microbiology, 2025)
The interplay between gut microbiota and sarcopenia has emerged as a cutting-edge research topic in the medical field, garnering significant attention. Sarcopenia is an age-related syndrome characterized by a progressive decline in skeletal muscle mass, strength, and function, which profoundly impacts the quality of life in older adults and imposes substantial socioeconomic burdens on many counties. Accumulating evidence indicates that alterations in the gut microbiota are not only linked to various intestinal disorders but also to aging-associated conditions, such as sarcopenia. The gut microbiota plays a pivotal role in regulating skeletal muscle homeostasis via its metabolic products and is increasingly recognized as a potential pathophysiological factor contributing to sarcopenia development. Skeletal muscle, functioning as both a motor and endocrine organ, secretes myokines that exert critical regulatory effects on the gut microbiota. In sarcopenic individuals, reduced secretion of myokines correlates with decreased microbial diversity and compositional shifts, marked by diminished beneficial microbes and increased potentially harmful species. This establishes a vicious cycle of gut dysbiosis-sarcopenia-gut dysbiosis. Modulation of the gut microbiota has been demonstrated to enhance muscle mass and function in elderly patients with sarcopenia. Metabolites derived from the gut microbiota, such as amino acids, lipopolysaccharides, and short-chain fatty acids, are known to modulate skeletal muscle protein metabolism by influencing anabolic and catabolic pathways. Nevertheless, the bidirectional mechanisms underlying the relationship between gut microbiota and age-related sarcopenia remain incompletely understood. In this review, we aim to: (1) integrate current knowledge regarding the bidirectional interaction between sarcopenia and gut microbiota; (2) summarize existing management strategies for age-related sarcopenia based on this interaction.